Investigating change in students' beliefs about English language learning after attending tuition aid scheme program / Mohd Junaidi Mohd Mukhtar - Mohd Mukhtar, Mohd Junaidi (2012)
The government of Malaysia spent about RM200 million so far in financing Tuition Aid Scheme program which was started in the year 2004. The program was designed to assist poor and weak primary students to improve their achievements in Bahasa Melayu,English, Mathematics and Science subjects. Since it is a new program introduced by Malaysia Ministry of Education its impact on students' beliefs about English language learning after joining this English tuition is not yet revealed by any study.Therefore, this issue led the researcher to conduct a small study in order to seek answer of whether this program could really give significant impact to students' beliefs. By combining quantitative (through questionnaire) and qualitative (through personal interview) research approach, the researcher used a sample of 112 primary students from 10 selected schools around Kuala Terengganu district as sample in this study. The students' responses from the questionnaire administered before and after joining the program were compared and justified by the personal interview conducted. The study showed that the significant change existed in students' beliefs about English language learning after joining the TAS program for about a year. The result also revealed that their English achievement and English daily usage increased steadil y. The results from this study are important to Malaysia government in considering the decision to continue and extend this program in the future. For the English teachers who involved directly with this program, these positive results will make them feel proud and motivated to continue this program.